Epigenetic studies and pediatric research. - Bellanti, Joseph A. (Pediatric Research, 2020)
The 2020 Annual Review Issue, "Preventing Disease in the 21st Century" was selected by the Editors-in-Chief of Pediatric Research to include a variety of disease entities that confront health-care practitioners entrusted to the care of infants and children. In keeping with this mandate, this article reviews the subject of epigenetics, which impacts pediatric research from bench to bedside. Epigenetic mechanisms exert their effects through the interaction of environment, various susceptibility genes, and immunologic development and include: (1) DNA methylation; (2) posttranslational modifications of histone proteins through acetylation and methylation, and (3) RNA-mediated gene silencing by microRNA (miRNA) regulation. The effects of epigenetics during fetal life and early periods of development are first reviewed together with clinical applications of cardiovascular and metabolic disorders in later life. The relationships of epigenetics to the allergic and autoimmune diseases and cancer are next reviewed. A specific focus of the article is directed to the recent recognition that many of these disorders are driven by aberrant immune responses in which immunoregulatory events are often poorly functioning and where through interventive epigenetic measures prevention may be possible by alterations in programming of DNA during fetal and early periods as well as in later life.